1996
DOI: 10.1007/bf01396209
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of deep venous thrombosis in the lower extremities of children in the intensive care unit

Abstract: Children in an ICU setting are at significantly lower risk for thrombosis than adults in the same setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Interestingly, there are multiple reviews in the pediatric and adult literature citing an increased DVT rate with femoral catheters [6,[23][24][25][26][27][28][29][30]. In studies that separate patients by age, smaller patients (b1 year old) are found to have a higher incidence of femoral CVC-associated DVTs than any other group [5,6].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, there are multiple reviews in the pediatric and adult literature citing an increased DVT rate with femoral catheters [6,[23][24][25][26][27][28][29][30]. In studies that separate patients by age, smaller patients (b1 year old) are found to have a higher incidence of femoral CVC-associated DVTs than any other group [5,6].…”
Section: Discussionmentioning
confidence: 94%
“…[4][5][6][7] DVT occurs less frequently in children than in adults, but when it does, it has the same potential for pulmonary embolization and death. [8][9][10][11][12] Anticoagulation with heparin and Coumadin is standard therapy for the treatment of DVT in children, just as it is in adults. Occasionally, however, anticoagulation therapy is ineffective in protecting against a pulmonary embolism or is contraindicated because of hemorrhage or recent trauma.…”
Section: Methodsmentioning
confidence: 99%
“…[2,3,19,20] Several publications have reported VTE rates in the hospitalized pediatric population [2,3,[21][22][23] and in the intensive care population. [20,24,25] To date, no study has investigated the pediatric inpatient surgical population as a whole while comparing rates between procedures and subspecialties.…”
Section: Overall Vte Rates and Timing To Vtementioning
confidence: 99%